PKS B1740-517: an ALMA view of the cold gas feeding a distant interacting young radio galaxy. Issue 3 (24th October 2018) - Allison, J R; Mahony, E K; Moss, V A; Sadler, E M; Whiting, M T; Allison, R F; Bland-Hawthorn, J; Curran, S J; Emonts, B H C; Lagos, C D P; Morganti, R; Tremblay, G; et al.
ABSTRACT: Cold neutral gas is a key ingredient for growing the stellar and central black hole mass in galaxies throughout cosmic history. We have used the Atacama Large Millimetre Array to detect a rare example of redshifted 12 CO (2–1) absorption in PKS B1740–517, a young ( t ∼ 1.6 × 10 3 yr) and luminous ($L_{\rm 5\, GHz} ≈ 6.6 × 10^{43}$ erg s −1 ) radio galaxy at $z$ = 0.44 that is undergoing a tidal interaction with at least one lower mass companion. The coincident H i 21-cm and molecular absorption have very similar line profiles and reveal a reservoir of cold gas ( M gas ∼ 10 7 −10 8 M⊙ ), likely distributed in a disc or ring within a few kiloparsecs of the nucleus. A separate H i component is kinematically distinct and has a very narrow line width (Δ$v$ FWHM ≲ 5 km s −1 ), consistent with a single diffuse cloud of cold ( T k ∼ 100 K) atomic gas. The 12 CO (2–1) absorption is not associated with this component, which suggests that the cloud is either much smaller than 100 pc along our sight line and/or located in low-metallicity gas that was possibly tidally stripped from the companion. We argue that the gas reservoir in PKS B1740–517 may have accreted on to the host galaxy ∼ 50 Myr before the young radio AGN was triggered, but has only recently reached the nucleus. This is consistent with the paradigm that powerful luminous radio galaxies are triggered by minor mergers and interactions with low-mass satellites and represent a brief, possibly recurrent, active phase in the life cycle of massive early-type galaxies.